The Effect Of Addition Pumpkin (Cucurbita MoschataD.) Flour In Artificial Diet To The Color Quality Of Goldfish (Carrasius Auratus) - Sausan Nazhira; Safrida Safrida; Muhammad Ali Sarong (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2017)
The ornamental fish price is determined by the appearance of colour. Feeding naturally feed in artificial feed aimed to improve the color quality of goldfish and how long it takes to improve the color. This research was used experimental method with quantutative approach. Research used CRD (Complete Random Design) which consists of 4 treatments with different concentration includes: P0: Positive control, P1: 5%, P2: 10%, and P3: 15%, with 5 replications in each treatments. Parameter in this research are color quality improvements, length and weight accretion for 6 weeks which measured in the first, second, third, fourth, fifth and sixth week. The research result showed that feeding the pumpkin flour in artificial diet affected the color improvement of goldfish but did not affect the length and weight of goldfish. The optimal color improvement of goldfish obtained on the treatment with 15% concentration. A summary of this research is feeding the pumpkin flour in artificial diet on 42 days affected the color improvement of goldfish but did not affect the length and weight of goldfish.